Pemilihan Ibukota Negara Republik Indonesia Baru Berdasarkan Tingkat Kebencanaan - Kurniadi, Anwar (Republic of Indonesia Defense University, 2019)
The consideration to removal of Indonesia Republic United States capital has happened to four presidentâ€™s era, Soekarno, Soeharto, Susilo Bambang Yudhoyono, and Joko Widodo, the removal of Indonesia capital were due to economical and political reasons. Other reasons was less of environment capacity to support capitalâ€™s activities. This condition It showed by rising traffic jam, polutions and often happened flood disaster. The purpose of this paper is to analize the capital requirenment from disaster analysis, disaster risk, and disaster potent. The method used literature review Â with using data analize of Mile and Huberman. Results and discussion showed that all provinces the South Kalimantan, the Center Kalimantan and the East Kalimantan have same disaster, like as forest fire forest especialy from peat, drought, rob flood, earthquake, and also tsunami. However, the province of the South Kalimantan, on fact, It has the most minimal of disaster risk and disaster potent. The conclusion was the South Kalimantan would be the first choice to be the new of Indonesia Capital from disaster analysis aspect at where the most minimal of risk and potent of disasters.